TYPOLOGY OF ETHNIC STEREOTYPES IN RUSSIAN PROVERBS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
The article highlights the reflection of stereotypes in Russian proverbs and sayings. In the center of attention are atostereotypes and hetero stereotypes as a variety of national stereotypes.